Corporate Culture in Nepalese Hotel Industry - Pokharel, Shiva Prasad; Pokhrel, Bishnu Prasad (Cognition, 2019)
The competing values framework was used to describe the organizational culture type exhibited by Nepalese listed five star hotel’s managers. This framework assesses the dominant organizational culture based on four culture types: Clan, Hierarchy, Adhocracy, and Market. Nepalese hotels managers exhibited different culture type as dominant in both the current and preferred situations on the basis of dominant characteristics, organizational leadership, managements of employee, organizational glue, strategic emphases and criteria of success. The purpose of the study was to examining the values preferred and now by managers at listed hotels in Nepal, in the context of these above mention types of organizational culture. The methods used for identification of the dominant types of organizational culture is organizational culture assessment instruments (OCAI) which is based on the Competing Values Framework developed by Cameron and Quinn, 1999 The study suggests implications for extension nationwide.